2019
DOI: 10.1530/eje-19-0389
|View full text |Cite
|
Sign up to set email alerts
|

Will biological agents supplant systemic glucocorticoids as the first-line treatment for thyroid-associated ophthalmopathy?

Abstract: In this article, the two authors present their opposing points of view concerning the likelihood that glucocorticoids will be replaced by newly developed biological agents in the treatment of active, moderate-to-severe thyroid-associated ophthalmopathy (TAO). TAO is a vexing, disfiguring and potentially blinding autoimmune manifestation of thyroid autoimmunity. One author expresses the opinion that steroids are nonspecific, frequently fail to improve the disease and can cause sometimes serious side effects. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 128 publications
(157 reference statements)
0
17
0
Order By: Relevance
“…More recent reports suggest that IV pulse may be more effective and associated with fewer side effects than those delivered by the oral route ( 41 ). But even staunch advocates of steroid use in TAO typically concede that these agents fail to consistently provide benefit to patients and that only 50% respond meaningfully ( 42 ). Further, many experts acknowledge that responses to steroids are essentially limited to amelioration of inflammatory signs and symptoms.…”
Section: Tao Has Long Been a Disease The Treatment For Which Exemplifmentioning
confidence: 99%
“…More recent reports suggest that IV pulse may be more effective and associated with fewer side effects than those delivered by the oral route ( 41 ). But even staunch advocates of steroid use in TAO typically concede that these agents fail to consistently provide benefit to patients and that only 50% respond meaningfully ( 42 ). Further, many experts acknowledge that responses to steroids are essentially limited to amelioration of inflammatory signs and symptoms.…”
Section: Tao Has Long Been a Disease The Treatment For Which Exemplifmentioning
confidence: 99%
“…After publication of the 2016 European Thyroid Association (ETA)/European Group on GO (EUGOGO) guidelines for the management of GO (8), several relevant studies have been published, particularly randomized clinical trials (RCTs) of newer biological agents for the treatment of moderate-to-severe and active GO (1, [9][10][11][12]. This prompted the EUGOGO Executive Committee to appoint an ad hoc task force committed to updating the guidelines, focusing on the medical management of GO.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned above, our study also found no significant difference of the rate of proptosis improvement between the two regimens. e underlying mechanism is yet to be completely elucidated; it might be that the patient's orbital remodeling and Journal of Ophthalmology eventual fibrosis occur very early in the course of the disease, so there is no hope that whatsoever medical treatment be effective if these changes have taken place [28]. Although effective, GC treatment is not devoid of adverse events [12,29].…”
Section: Discussionmentioning
confidence: 99%